Raptors : a fistful of daggers [videorecording (DVD)] - Hamilton, Matt (Matthew Charles); Nyambi, Nyambi (PBS Distribution, 2024)
The planet's most successful large predators are a group of birds known as raptors. United by a hooked beak, a taste for flesh and a set of razor-sharp talons, these birds of prey have conquered the globe. Raptors dominate every habitat in which they live. Learn more about eagles, hawks, and falcons as well as the lesser-known hunters like the secretary bird, the caracara, kites and more.